2000
DOI: 10.3109/10428190009054882
|View full text |Cite
|
Sign up to set email alerts
|

Disease Features in Acute Myeloid Leukemia with t(8;21)(q22;q22). Influence of Age, Secondary Karyotype Abnormalities, CD19 Status, and Extramedullar Leukemia on Survival

Abstract: Over a period of 14 years, 50 patients (12 children and 38 adults) of whom 46 had acute myeloid leukemia (AML) and 4 had myelodysplastic syndrome characterized by the t(8;21)(q22;q22) translocation were referred to the Royal Marsden Hospital. The clinicopathological features of these cases were analyzed to determine the influence of age, secondary karyotype abnormalities, and expression of the lymphoid marker CD19 on event free survival, and presence of extramedullary leukemia on overall survival. They were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
36
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 18 publications
6
36
0
6
Order By: Relevance
“…Notably, the loss of a sex chromosome and deletion of chromosome 9q are most common and their impact on survival is controversial. 1,5,15,[17][18][19][20] In this study, we confirmed that the loss of a sex chromosome and del(9q) were common, in 22 (39%) and six (11%) cases, respectively, and these aberrations did not correlate with poorer clinical outcome. These results are in keeping with the observations by other investigators who had 4100 cases in their respective study series.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Notably, the loss of a sex chromosome and deletion of chromosome 9q are most common and their impact on survival is controversial. 1,5,15,[17][18][19][20] In this study, we confirmed that the loss of a sex chromosome and del(9q) were common, in 22 (39%) and six (11%) cases, respectively, and these aberrations did not correlate with poorer clinical outcome. These results are in keeping with the observations by other investigators who had 4100 cases in their respective study series.…”
Section: Discussionsupporting
confidence: 72%
“…The strength of our series is that the large majority of newly diagnosed patients were treated similarly in a single institution instead of multiple different protocols as in earlier large series, allowing us to assess the prognostic factors across different subgroups despite the relatively small cohort size. The del(9q) was identified as a negative 16 or positive 18 prognostic factor in one study each. In the former study, 7 of 50 patients with del(9q) had a median OS of 12.5 months.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…AML1-ETO is a fusion protein transcription factor generated from t(8;21)(q22;q22). This translocation is identified in Ͼ10% of all cases and up to 40% of the French-American-British M2 subtype of AML (2)(3)(4)(5). However, expression of AML1-ETO by itself fails to cause leukemia (6)(7)(8)(9)(10)(11), which suggests the requirement of ''additional hits'' for AML1-ETO-positive cells to become leukemogenic.…”
mentioning
confidence: 99%